Dance movement psychotherapy with people with learning disabilities out of the shadows, into the light - Unkovich, Geoffrey; Butté, Céline; Butler, Jacqueline (Milton Park, Abingdon, Oxon Routledge, 2017)
"This book provides an overview of dance movement psychotherapy for young people and adults with learning disabilities. Contributors from a variety of backgrounds examine their work with clients from across the disabilities spectrum, ranging from mild to complex needs.　The book chapters present theory and practice relating to the client group and subsequent therapy processes"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dance therapy; Authentic movement (Dance therapy).; Learning disabled -- Rehabilitation; Dance for people with disabilities; Movement therapy